Epitaxial growth of large-grain-size ferromagnetic monolayer CrI3 for valley Zeeman splitting enhancement. Issue 5 (28th January 2021) - Gong, Lipeng; Zhang, Cheng; Nie, Anmin; Lin, Changqing; Zhang, Hao; Gao, Chaofeng; Wang, Meng; Zhang, Xi; Han, Nannan; Su, Huimin; Lin, Chen; Jin, Yizheng; et al.
Abstract : The mass production of flower-like CrI3 monolayer on mica is achieved by a confined vapor epitaxy method. Abstract : Two-dimensional (2D) magnetic CrI3 has received considerable research attention because of its intrinsic features, including insulation, Ising ferromagnetism, and stacking-order-dependent magnetism, as well as potential in spintronic applications. However, the current strategy for the production of ambient-unstable CrI3 thin layer is limited to mechanical exfoliation, which normally suffers from uncontrollable layer thickness, small size, and low yet unpredictable yield. Here, via a confined vapor epitaxy (CVE) method, we demonstrate the mass production of flower-like CrI3 monolayers on mica. Interestingly, we discovered the crucial role of K ions on the mica surface in determining the morphology of monolayer CrI3, reacting with precursors to form a KI x buffer layer. Meanwhile, the transport agent affects the thickness and size of the as-grown CrI3 . Moreover, the Curie temperature of CrI3 is greatly affected by the interaction between CrI3 and the substrate. The monolayer CrI3 on mica could act as a magnetic substrate for valley Zeeman splitting enhancement of WSe2 . We reckon our work represents a major advancement in the mass production of monolayer 2D CrI3 and anticipate that our growth strategy may be extended to other transition metal halides.